TRUNK ASYMMETRY AND SPRUCE WOOD RESONANT PROPERTIES VARIABILITY WITH RESPECT TO THE CARDINAL POINTS AND THE TREE HEIGHT - Fedyukov, Vladimir; Saldaeva, Ekaterina; Chernova, Maria; Chernov, Vasilii (Journal of Applied Engineering Science, 2017)
Decks of musical instruments are developed from sawn wood products of strictly radial cutting and, as a rule, for this purpose the wood is selected according to the radius of a trunk from a certain forest site. An important factor for manufacturing high-quality (custom-made) musical instruments is the account of position of the best zone of a tree trunk with respect to the cardinal points. Observance of this condition becomes complicated by the fact that frequently trunks have the form of an abnormal cylinder with a displaced and curved axis (asymmetry). Physical and mechanical properties of wood vary greatly along trunk height; it is sometimes difficult to define the part of trunk wood with the best acoustic parameters. The paper presents the following research results: external and internal asymmetry of spruce trunks; macrostructures and acoustic constants of wood on northern and southern sides of a trunk; changes of cross-section sound velocity in wood along tree height and depending on the trunk diameter; dependence of sound velocity in wood on biometric data of a trunk. Based on the results of the work done, the estimation of cardinal points and position of wood at trunk height influencing the parameters of its ‘musicality’ is made. The data obtained and conclusions of the research are of scientific interest and bear practical recommendations for correct selection of wood with unique acoustic properties from a spruce-tree trunk.
Keywords: Wood density; Wood macrostructure; Spruce growing; Resonant properties; Internal and external tree trunk asymmetry; Ascoustic constant